Chemotherapy induced nail changes - Gupta Aashima; Parakh Ankit; Dubey Anand (Wolters Kluwer Medknow Publications, 2008)
Anticancer chemotherapy is associated with a variety of nail changes. We present two children who developed different nail changes, while receiving almost similar antineoplastic drugs.